A Study of Fetomaternal Outcome in Relation to Major Degree Placenta Previa: An Experience at a Tertiary Care Hospital - Shazia Tabassum, Rabeea Sadaf, Nasreen Kishwar, Zahida Parveen, Samreen, Saman Mudassir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Placenta previa is one of the major causes of antepartum hemorrhage. Although placenta previa accounts for approximately 0.4 – 0. % of all pregnancies, still it remains a major cause of fetomaternal morbidity and mortality. Aim: To determine the incidence of major degree placenta previa and its relation to fetomaternal outcome in a tertiary care hospital. Methods: This is a prospective observational study which was carried out in the department of Obstetrics and Gynecology Hayatabad medical complex, a tertiary care hospital in Peshawar Khyber Pakhtunkhwa from January 2022 to December 2022. Study was started after ethical approval was taken from institutional ethical committee. Total 35 pregnant women with ultrasonographic diagnosis of major degree placenta previa were enrolled in the study after fulfilling inclusion and exclusion criteria. Detailed history was taken, relevant Obstetrical examination was performed and relevant baseline labs and pre-op workup was done. All the relevant data was entered in a predesigned proforma and fetomaternal outcome was studied in addition to the incidence of major degree placenta previa. Results: Total no. of deliveries were 5712 in the study period. Total number no. of major degree placenta previa were 35 making its incidence as 0.6%. In present study majority of the patients presented between age 21-35 years. All the patients with a diagnosis of major degree placenta previa were multigravida and there was no single case of primigravida in the present study. Majority patients were unbooked. Majority of the patients ended up in emergency C/Section due to massive bleeding episode. Previous C/Section was the most important risk factor found in present study. 29 women required blood transfusion, 5 women had accidental diagnosis of the morbidly adherent placenta and cesarean hysterectomy was done in 4 cases. Uterine packing was done in 16 cases. There was no maternal mortality in the present study. Majority of the patient delivered between 33-36 weeks of gestation and majority of the babies had a birth rate of > 2.5Kg. Practical implication Patients with or without previous history of cesarean section and with major degree placenta previa diagnosed on ultrasonography should be booked and admitted earlier in Tertiary Care Hospital with all pre-op preparation to prevent maternal morbidity and mortality and better neonatal outcome. Conclusion: The higher fetomaternal morbidity and mortality, associated with placenta previa can definitely be curtailed by early antenatal diagnosis of placenta previa, advance planning, timely referral, delivery at a tertiary care hospital with availability of round the clock blood bank facility, NICU facility and obstetric ICU / HDU facility. Keywords: Major degree Placenta previa, maternal mortality, perinatal mortality, fetomaternal morbidity.